2021
DOI: 10.1002/mgg3.1834
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐exome sequencing identified first homozygous frameshift variant in the COLEC10 gene in an Iranian patient causing 3MC syndrome type 3

Abstract: Background: 3MC syndrome type 3 is an autosomal recessive disorder caused by mutations in the COLEC10 gene besides other genes like COLEC11 and MASP1.This disorder is characterized by facial dysmorphism, cleft lip and palate, postnatal growth deficiency, cognitive impairment, hearing loss, craniosynostosis, radioulnar synostosis, genital and vesicorenal anomalies, cardiac anomalies, caudal appendage, and umbilical hernia. Methods:In the present study, whole-exome sequencing was performed in order to identify d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The WES raw data (FastQ file) was analyzed by bioinformatics tools based on similar studies (Mohammadi, Daneshmand, et al, 2021 ; Mohammadi, Heidari, et al, 2021 ; Mohammadi, Salehi Siavashani, et al, 2021 ). The FastQC was used to perform quality control (QC) of reads based on GC content and Phred value (Gaur & Chaturvedi, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The WES raw data (FastQ file) was analyzed by bioinformatics tools based on similar studies (Mohammadi, Daneshmand, et al, 2021 ; Mohammadi, Heidari, et al, 2021 ; Mohammadi, Salehi Siavashani, et al, 2021 ). The FastQC was used to perform quality control (QC) of reads based on GC content and Phred value (Gaur & Chaturvedi, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Whole exome sequencing and bioinformatics analysis was preformed as described previously [ 7 ]. Called variants were filtered considering minor allele frequency (MAF) > 0.01 based on the Gnome Aggregation Database (gnomAD v3) Consortium, and Iranome population databases [ 8 , 9 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Variable features were reported that included short stature, blepharoptosis and epicanthus inversus, cleft lip/palate, congenital heart and kidney malformations, and skeletal anomalies of the digits, including clinodactyly and polydactyly. In these five patients, five novel variants were identified, including both loss of function variants and missense variants (Migliorero et al, 2021; Mohammadi et al, 2021; Munye et al, 2017). Here we describe nine individuals, from five separate families, with homozygosity of the c.311G > T (p.Gly104Val) variant in COLEC10 (NM_006438.3) and variable features of 3MC syndrome.…”
Section: Introductionmentioning
confidence: 99%